The feasibility of online video calling to engage patients with cystic fibrosis in exercise training. (July 2020) - Tomlinson, Owen W; Shelley, James; Trott, Jayne; Bowhay, Ben; Chauhan, Rohan; Sheldon, Christopher D
Introduction: Physical activity, including structured exercise, is an essential component in the management of cystic fibrosis. The use of telehealth such as video-calling may be a useful method for the delivery of exercise and physical activity interventions, though the feasibility of this remains unknown. Methods: Nine patients with cystic fibrosis (three female, six male, 30.9 ± 8.7 years) volunteered to participate. Participants completed an eight-week exercise training intervention conducted via Skype, using personalised exercises, with all sessions supervised by an exercise therapist. Feasibility was assessed by demand, implementation, practicality and acceptability. Changes in anthropometric, pulmonary, physical activity and quality of life variables were also assessed. Results: Two male participants withdrew from the study, citing lack of available time. The remaining participants found use of Skype useful, with a mean satisfaction rating of 9/10, and three participants requesting to continue the sessions beyond the duration of the study. Mean compliance with sessions was 68%, with mean duration of sessions being 20 min. A total of 25% of calls suffered from technical issues such as video or audio lags. Anthropometric, pulmonary, physical activity and quality of life variables remained unchanged over the course of the study period. Discussion: The use of Skype to deliver an exercise intervention to patients withcystic fibrosis was found to be technologically feasible, and acceptable among participants. Findings have implications for clinical practice and could allow care teams to engage patients remotely in exercise. Further research is required to assess the efficacy of this modality on increasing physical activity and associated health outcomes.